The Meaning Of Qualisign Signs In Tere Liye's Novel Bumi And Its Implication For Literature Learning In Vocational Schools - B. Syukroni Baso; Johar Amir; Kembong Daeng (International Forum of Researchers and Lecturers, 2022)
This research aims to analyze the meaning of qualisigns in the novel Bumi by Tere Liye and its implications for literature learning in vocational schools (SMK). The research method used is qualitative descriptive with semiotic analysis technique. The data used are quotations from the novel Bumi that contain qualisigns. The results show that qualisigns in the novel Bumi have various meanings, such as attentive, polite, angry, and others. These signs are presented by the author as a representation of the characters or situations presented in the novel. The quotations that become the focus of the study, namely